In Vivo Imaging of Hepcidin Promoter Stimulation by Iron and Inflammation - Flanagan, Jonathan M. (2007)
Hepcidin is an acute-phase response antimicrobial peptide that has emerged as a central regulator of iron absorption. Circulating hepcidin levels have been shown to affect iron uptake, release and storage. Hepcidin is mainly liver-derived and regulated, at least in part, transcriptionally. Hypoxia, erythroid demand, iron content and inflammation each have been shown to influence hepcidin mRNA expression in intact animals. In vitro, regulation of hepcidin by cytokines and by hypoxia is readily demonstrated in primary hepatocytes or in hepatocyte lines, but incubating the same cell lines with iron does not increase transcription of hepcidin. Thus, how iron excess stimulates hepcidin production in hepatocytes remains unknown. In addition, there is no current technique available that can investigate how iron induces hepcidin expression. To provide a better understanding of hepcidin gene expression in response to these regulatory stimuli, we have established a whole animal in vivo bioluminescence imaging assay to measure the activity of hepcidin promoter constructs in the animals liver after hydrodynamic transfection of hepcidin promoter/luciferase constructs into mice. Transfected hepcidin promoter constructs were shown to respond to both inflammatory and increasing iron stimuli in vivo. This work highlights the ability of this new imaging technique to investigate the key regions of the hepcidin promoter involved in iron induction of hepcidin expression.